(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2023)
The purpose of the study is the study the immune status of patients with hemophilia. A complex of immunological studies aimed at determining individual populations and immunoregulatory subpopulations of lymphocytes was carried out in 45 patients with hemophilia, of which 25 suffered from a severe form and 20 were diagnosed with an average form of hemophilia. 16 practically healthy men were examined as a control group. The research results show that hemophilia is accompanied by a violation of the immune status in patients, which manifests itself in changes in the cellular link (a sharp decrease in the total pool of T-lymphocytes and its subpopulation - TGF ( theophylline-resistant ) cells, with significantly high values of THF ( theophylline-sensitive ) cells and humoral immunity (increase in the content of B-lymphocytes, severe dysimmunoglobulinemia with a decrease in the content of immunoglobulin A and an increase in the level of immunoglobulins M and G). Data from studies of FAN (phagocytic activity of neutrophils) and CEC (circulating immune complexes) also confirm the fact of impaired immunoreactivity in patients with hemophilia: FAN values are reduced, increasing CEC.